Chemical capture of free-ranging red deer (Cervus elaphus) with medetomidine-ketamine - Arnemo, J.M.; Negard, T.; Søli, N.E. (Rangifer, 1994)
Seventeen free-ranging red deer (Cervus elaphus) (12 calves and 5 yearling hinds) were immobilized with a combination of medetomidine hydrochloride (MED) and ketamine hydrochloride (KET) in winter (January-March). Immobilizations were performed with plastic projectile syringes fired from a dart gun. Mean (SD) doses of 0.147 (0.024) mg MED/kg and 2.5 (0.4) mg KET/kg induced recumbency in 5.0 (2.0) minutes in the calves and all of them were completely immobilized. The initial doses in the yearling hinds were 0.099 (0.016) mg MED/kg and 1.9 (0.2) mg KET/kg but three of them required addirional dosing for induction of reliable restraint. The distance covered by the animals between darting and recumbency ranged from 40-250 m for calves and 100-300 m for yearling hinds. The animals were translocated to deer farms for breeding purposes and were given 12.5-25.0 mg of atipamezole hydrochloride before transportation. All animals recovered completely. Haematological and serum biochemical comparisons between free-ranging calves immobilized with medetomidine-ketamine (n=3) and captive unmedicated calves (n=4) showed that chemical capture induce very little stress in red deer.
Keywords: red deer; immobilization; haematology; serum biochemistry; Cervidae